Study of Feeding with Local Raw Materials with Different Protein for Growth Sultana Tilapia (Oreochromis niloticus) - Sinaga, Edward Gracelado; Hudaidah, Siti; Santoso, Limin (Fakultas Perikanan dan Kelautan Universitas Riau, 2021)
Tilapia (Oreochromis niloticus) strain of Sultana (superior selection of salabintana) is a new variety developed by the Center for Freshwater Resources Development (BBPABT) Sukabumi, West Java. Sultana tilapia is the result of crossing 10 superior varieties such as gift tilapia, jica, white, and other superior tilapia. Many factors cause the high price of feed, one of which is dependent on imported raw materials for feed manufacture. This study aims to assess the effectiveness of the use of local raw materials with different protein content in feed for the growth of tilapia and reduce production costs by using local raw materials as feed ingredients. This research was conducted from March 21 to June 19, 2020 at the Integrated Field Laboratory of the Faculty of Agriculture, University of Lampung. The design used in this study was a completely randomized design (CRD) consisting of four treatments with three replications. The treatments given included 30% protein treatment (A), 33% protein treatment (B), 36% treatment (C), and commercial feed control (D) for 60 days of maintenance. The data obtained were analyzed by using the ANOVA test and followed by the Duncan test. The results obtained in this study are that treatment B has the best FCR value and is significantly different compared to other treatments so as to produce the best growth. Besides that, treatment A and C also had a significantly different FCR value compared to the control.